Útgarðaloki und die Britischen Inseln - Egeler, Matthias (Snorri Sturluson - Historiker, Dichter, Politiker, 2013)
Within the history of Norse scholarship, a considerable number of the mythological motifs treated in Snorri’s Edda have at one time or another been connected with motifs found in the Celtic literatures and folklore of Britain and Ireland. The spectrum of proposed Celtic borrowings ranges from details as minor as the boar Sæhrímnir in Valhalla to elements as central as the death of Balder. Arguably the most-discussed of these proposed Celtic-Norse connections is the tale of Thor’s visit to Útgarðaloki (Gylfaginning 44–47). The present article discusses the hypothesis of a Celtic origin for the Útgarðaloki-narrative from a primarily historiographical and methodological perspective. Beginning with the work of Carl Wilhelm von Sydow, it addresses the fundamental methodological problems that characterise much older comparative research on possible Celtic influences in Norse mythology, and illustrates how these problems led to a growing scepticism towards such approaches in the last decades of the 20th century. At the same time, however, the article challenges the need for a fundamental scepticism towards the question of Celtic influences in general. In order to provide a viable alternative, it draws attention to the largely overlooked work of Rosemary Power, who in an exemplary article on the events in the hall of Útgarðaloki demonstrated the possibility of a methodologically sound approach to the question of Celtic influences in Norse mythology. Building on Power’s approach, the article then turns to one of the insular Celtic parallels to the resuscitation of Thor’s goats in Gylfaginning 44, tentatively arguing that this motif might indeed be a Celtic borrowing, but suggesting a new interpretation of the historical context in which the borrowing occurred. The discussion concludes by proposing some general methodological guidelines for approaching the question of Celtic influences in Norse mythology.